Wicked forest - Andrews, V. C. (Virginia C.) (New York : Pocket Books, 2002)
Willow DeBeers leaves her North Carolina town to make a new start with her mother and half-brother in Palm Beach, Florida.
Accelerated Reader AR
Keywords: Adoptees -- Fiction; Rich people -- Fiction; Palm Beach (Fla.) -- Fiction